Modelling the Dynamics of Tuberculosis A Multi-Stage Compartmental Approach - Adetayo Samuel Eegunjobi (Journal of Mathematical and Fundamental Sciences, 2025)
We propose a robust multi-stage compartmental model to studytuberculosis (TB) transmission dynamics in Namibia, incorporating multiple stagesof latent infection, along with undiagnosed and diagnosed active cases. The modeldistinguishes between early and late latent stages, allowing for a more accuraterepresentation of TB progression. By capturing the complex interactions betweendisease progression, diagnosis, treatment, and relapse, the model provides valuableinsights into TB dynamics. Mathematical analyses and key simulation parametersare discussed, offering a framework that can inform public health strategies foreffective TB control and intervention in Namibia.